ANALISIS TINDAK TUTUR DALAM NOVEL MERANTAU KE DELI KARYA PROF. DR. HAMKA - Yolenta Anda; Dewa Gede Bambang Erawan; I Gusti Ayu Putu Tuti Indrawati (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2022)
This research is a qualitative descriptive study that discusses the study of pragmatics seen from the aspect of speech acts. The purpose of this study was to determine the speech acts of locutions, illocutions and perlocutions, in the novel Merantau Ke Deli by Prof. Dr. Hamka. Data collection methods in this study are reading, taking notes and literature study. The data analysis method used in this study is to reduce data, present data and verify and conclude data. The results of the speech act research in the novel Merantau Ke Deli by Prof. Dr. Hamka has fifty utterances including twenty-eight locutionary speech acts, namely eight statement locutions, fourteen question locutions, six command locutions. The illocutionary speech acts found there are ten utterances including one representative illocutionary, one commissive illocutionary, four directive illocutions, two expressive illocutions , two declarative illocutions. The perlocutionary speech act in the novel Merantau Ke Deli by Prof. Dr. Hamka has twelve perlocutionary utterances. The causal factors used are locutionary, illocutionary, and perlocutionary speech including showing promise or ability, flattery or praise, conveying intentions and prohibitions.